2012
DOI: 10.1111/j.1469-7580.2012.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

A computerized tomography study of the morphological interrelationship between the temporal bones and the craniofacial complex

Abstract: The hypothesis that the temporal bones are at the center of the dynamics of the craniofacial complex, directly influencing facial morphology, has been put forward long ago. This study examines the role of the spatial positioning of temporal bones (frontal and sagittal inclination) in terms of influencing overall facial morphology. Several 3D linear, angular and orthogonal measurements obtained through computerized analysis of virtual models of 163 modern human skulls reconstructed from cone-beam computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
10
1
1
Order By: Relevance
“…The results of these studies suggest that the largest component of secular changes in Americans is an increase in cranial vault height, with most of that change occurring in the cranial base. Other studies documented changes in cranial morphology and interesting interrelations between structures were observed in Austrians [5,16,23,37], Mexicans [30], Japanese [20,27], Croatians [14] and Portuguese [45]. The study by Weisensee KE, Jantz RL, 2011 [45] demonstrated a significant change in craniofacial morphology of the Portuguese from 1806 to 1954, with a decrease in facial breadth and a more inferiorly placed cranial base.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these studies suggest that the largest component of secular changes in Americans is an increase in cranial vault height, with most of that change occurring in the cranial base. Other studies documented changes in cranial morphology and interesting interrelations between structures were observed in Austrians [5,16,23,37], Mexicans [30], Japanese [20,27], Croatians [14] and Portuguese [45]. The study by Weisensee KE, Jantz RL, 2011 [45] demonstrated a significant change in craniofacial morphology of the Portuguese from 1806 to 1954, with a decrease in facial breadth and a more inferiorly placed cranial base.…”
Section: Discussionmentioning
confidence: 99%
“…By this method the influence and relationship could be evaluated not only in the linear measurement, but also in the projection of the A point and B point to the medial plane. Surprisingly, 70.1 % of the variation of the SNA angle in the eighteenth century could be explained by the orthogonal A variable, whereas in the nineteenth 42] and reproducibility [16,31] by applying a different computer-based software such as the one used in this study. Multiple regressions associated with the stepwise method regression analysis were used in the present study to identify the important craniofacial measurements that influenced the architecture of Portuguese skulls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, Costa et al 19 y Cendekiawan et al 20 relacionan los cambios en el área de la sincondrosis esfeno-occipital con cambios en la angulación de la base del cráneo. Por lo tanto, las variaciones en el ángulo SNFH y la longitud de la línea SN en pacientes con diferente patrón esquelético podrían estar directamente relacionadas con las diferentes modificaciones de la sincondrosis esfeno-occipital sobre la base craneal anterior durante el crecimiento y con el desplazamiento del punto nasion hacia adelante o en dirección vertical debido a los cambios en el proceso de remodelación.…”
Section: Discussionunclassified
“…[12][13][14][15][16] Knowing that occlusal sensitivity is within the range of 0.02-0.03 mm, 48,[50][51][52][53][54][55] that TMJ has a 'deflection' tolerance of only 0.6-0.8 mm, [12][13][14][15]49 and that the angular difference between the steepness of the articular eminence and the contra-lateral canine guidance of any skeletal class is ≤10°, [53][54][55] it becomes clear that dentistry is dealing with a highly individual and highly complex organ system. 3,[56][57][58]…”
Section: Guest Editorialmentioning
confidence: 99%